Проблемні питання застосування конструкції «юридична особа публічного права» - Жорнокуй, Ю. М.; Zhornokui, Yu. M.; Жорнокуй Юрій Михайлович (Право та інновації. - 2016. - № 4 (16). - С. 41-48, 2016)
У статті розглянуті питання проблематики застосування конструкції «юридична особа публічного права». Зазначається на дискусійності можливості існування юридичних осіб приватного та публічного права за критерієм поділу, що передбачений Цивільним кодексом України, у зв’язку з чим підтримується підхід про доцільність застосування одночасно декількох критеріїв поділу, одним із яких обов’язково має бути інтерес створення таких осіб. Проводиться порівняльний аналіз та доводиться різна спрямованість у створенні та діяльності юридичних осіб приватного та публічного права. Незважаючи на декларативність положень Конституції України про рівність форм власності, на прикладі корпоративних відносин зазначено, що юридичні особи публічного права все ж таки використовують власні переваги в тому числі й у приватних відносинах.

One of the controversial issues of modern civil law is not only recognition of a legal entity as a member of civil relations, but the existence of appropriate structure in general. Recently the idea of including a legal entity of public law into the system of civil law subjects has been supported. This idea found its consolidation in the provisions of the Civil Code of Ukraine. However, the relative construction has not got its detailed reasoning of expediency to be used within civil relations. Nowadays there are two opposite approaches to the recognition of the expediency to use the construction of «legal entity of public law». Some experts argue that it should be used in civil law (O. O. Pervomaiskyi, R. B. Sabodash, V. Ye. Chyrkyn, etc.), others – strongly deny this (S. M. Bratus, V. A. Bielov, Ye. O. Sukhanov, etc.). However, the works of these scholars do not provide a clear answer to the question of whether it is appropriate to single out a legal entity as an independent subject within civil relations along with a legal entity of private law. As a result of the existing problems there is a necessity to outline the issues of recognition of a legal entity of public law as a participant of civil relations. One of the urgent issues of separation of legal entities into those of private and public law is the criterion of relevant division. Regarding its election it has to be noted in the Civil Code of Ukraine that it, fist of all, should be considered not the procedure, but the objective of creation, and the scope, where any entity can act. Attention is paid to the interest during the establishment of legal entities. Despite the fact that the founder of legal entities of public law is the state legally represented by some agencies, where the interest is the same as in the creation of a legal entity of private law – the interest of the state, the legal entity, the interest of the society. Hence, legal entities of public law have no differences from legal entities of private law, since they act including according to their own (private) interest. Therefore, there is an inconsistence – the existence of public and legal status and, simultaneously, the private interest within legal entities. The state puts itself in a privileged position in the corporate relations, obliging legal entities of private law – corporations to distribute profis on the mandatory basis, despite the fact that the norms of corporate legislation provide binding decision on its distribution only at the general meeting of the corporate company. Our opponents may indicate that other participants (shareholders) of a business entity, which has corporate rights of the state in the authorized capital, receive dividends under the distribution of profis. However, why do the relevant norms are not applied to the rest of corporate companies, which do not have corporate rights belonging to the state in their authorized capital? Whether joint stock companies with the state share and corporations without such a share are different companies? Hence, we have more questions than answers. Despite the complexity and ambiguity of civil relations involving legal entities of public law, the current Ukrainian legislation does not regulate the features of such participation with the anticipation of certain means and guarantees of individual’s rights in these relations. conclusions and prospects for the development. Only those organizational and legal forms of legal entities should remain in civil law that can be created by individuals. This of course does not exclude the possibility of participation of legal entities of public law in the creation of legal entities of private law such as a joint-stock company or limited liability company. However, in this case, the state and its agencies will participate as individuals, fully responding the principle of civil law on their equal participation in private and legal relations.

В статье рассмотрены вопросы проблематики применения конструкции «юридическое лицо публичного права». Обращается внимание на дискуссионность возможности существования юридических лиц частного и публичного права в соответствии с критерием деления, который предусмотрен Гражданским кодексом Украины, в связи с чем поддерживается подход о целесообразности применения одновременно нескольких критериев деления, одним из которых обязательно должен быть интерес создания таких лиц. Проводится сравнительный анализ и доказывается разная направленность в создании и деятельности юридических лиц частного и публичного права. Учитывая декларативность положений Конституции Украины о равенстве форм собственности, на примере корпоративных отношений сделан вывод о том, что юридические лица публичного права все же используют собственные преимущества в том числе и в частных отношениях.
Проблемные вопросы применения конструкции «юридическое лицо публичного права»
Issues of implementing the construction «legal entity of public law»
Keywords: Цивільне право. Civil Law. Гражданское право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; юридичні особи приватного права; юридичні особи публічного права; інтерес; цивільні відносини; корпоративні відносини; legal entities of private law; legal entities of public law; interest; civil relations; corporate relations; юридические лица частного права; юридические лица публичного права; интерес; гражданские отношения; корпоративные отношения